Small interfering RNAs (siRNAs) in cancer therapy: a nano-based approach - Mahmoodi Chalbatani, Ghanbar (Int J Nanomedicine, 2019)
Cancer is one of the most complex diseases that has resulted in multiple genetic disorders and cellular abnormalities. Globally, cancer is the most common health concern disease that is affecting human beings. Great efforts have been made over the past decades in biology with the aim of searching novel and more efficient tools in therapy. Thus, small interfering RNAs (siRNAs) have been considered one of the most noteworthy developments which are able to regulate gene expression following a process known as RNA interference (RNAi). RNAi is a post-transcriptional mechanism that involves the inhibition of gene expression through promoting cleavage on a specific area of a target messenger RNA (mRNA). This technology has shown promising therapeutic results for a good number of diseases, especially in cancer. However, siRNA therapeutics have to face important drawbacks in therapy including stability and successful siRNA delivery in vivo. In this regard, the development of effective siRNA delivery systems has helped addressing these issues by opening novel therapeutic windows which have allowed to build up important advances in Nanomedicine. In this review, we discuss the progress of siRNA therapy as well as its medical application via nanoparticle-mediated delivery for cancer treatment.